ANALISIS KANDUNGAN MINERAL PASIR PANTAI DI KABUPATEN PACITAN DENGAN METODE EKSTRAKSI - Linda Silvia; Mochamad Zainuri; Suasmoro Suasmoro; Bintoro Anang Subagyo; Heru Sukamto; Mashuri Mashuri; Sri Yani Purwaningsih (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Pacitan is one of the region in East Java with very potential natural resources, one of which is beach sand. This is the basis for the analysis of mineral content on some beach sand in Pacitan by extraction method. Sand samples taken from Klayar beach, Banyu Tibo beach, Srau beach, and Watukarung beach. X-Ray Fluorescence (XRF) and X-Ray Diffraction (XRD) were employed to investigate the element composition and crystal structure of the prepared particles, respectively. The XRF results showed a largecalcium (Ca) content on the beach sand that is 91.18%, 93.07%, 94.84, and 94.88%, respectively while the rest is another element with a small percentage. The XRD results showed qualitatively the beach sand containing calcium carbonate(CaCO3) material which is one of the advanced material. CaCO3 can be used as an anticorrosive material, raw materials in the pharmaceutical industry, cosmetics, hydrophobic material, and the other applications. Keywords:sand, minerals, extraction, calcium carbonate, advanced material